2016
DOI: 10.18632/oncotarget.8867
|View full text |Cite
|
Sign up to set email alerts
|

MALT1 inhibitors prevent the development of DSS-induced experimental colitis in mice via inhibiting NF-κB and NLRP3 inflammasome activation

Abstract: Mucosa-associated-lymphoid-tissue lymphoma-translocation gene 1 (MALT1), a paracaspase and essential regulator for nuclear factor kB (NF-κB) activation, plays an important role in innate and adaptive immunity. Suppression of MALT1 protease activity with small molecule inhibitors showed promising efficacies in subtypes of B cell lymphoma and improvement in experimental autoimmune encephalomyelitis model. However, whether MALT1 inhibitors could ameliorate colitis remains unclear. In the present study, we examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 45 publications
4
56
0
Order By: Relevance
“…In further support of the above data, a recent paper by Liu et al (65) showed that the inhibition of mucosa-associated-lymphoid-tissue lymphoma-translocation gene 1 (MALT1), a scaffold protein, which recruits the IκB kinase complex leading to release and activation of NF-κB, ameliorated clinical symptoms and histopathologic features of DSS-induced colitis through NF-κB and NLRP3 inhibition, thus interfering with both inflammasome activation steps (65, 66). In particular, treatment with two specific MALT1 inhibitors, MI-2 and mepazine, dose-dependently attenuated the symptoms of colitis in mice through a decrease in protein and mRNA levels of colonic TNF, IL-1β, IL-6, IL-18, IL-17A, and IFN-γ pro-inflammatory cytokines (66).…”
Section: Pharmacological Modulation Of Nlrp3 Inflammasome In Bowel Insupporting
confidence: 74%
“…In further support of the above data, a recent paper by Liu et al (65) showed that the inhibition of mucosa-associated-lymphoid-tissue lymphoma-translocation gene 1 (MALT1), a scaffold protein, which recruits the IκB kinase complex leading to release and activation of NF-κB, ameliorated clinical symptoms and histopathologic features of DSS-induced colitis through NF-κB and NLRP3 inhibition, thus interfering with both inflammasome activation steps (65, 66). In particular, treatment with two specific MALT1 inhibitors, MI-2 and mepazine, dose-dependently attenuated the symptoms of colitis in mice through a decrease in protein and mRNA levels of colonic TNF, IL-1β, IL-6, IL-18, IL-17A, and IFN-γ pro-inflammatory cytokines (66).…”
Section: Pharmacological Modulation Of Nlrp3 Inflammasome In Bowel Insupporting
confidence: 74%
“…Malt1 expression and proteolytic activity are clearly important in mucosal homeostasis. Inhibition of Malt1 paracaspase activity with 2 distinct paracaspase inhibitors, MI‐2 and MPZ, protects mice during DSS‐induced colitis . This correlates with decreased NFκB and NLRP3 activation and decreased IL‐1β and IL‐18 production by PMA‐differentiated THP‐1 cells and bone marrow macrophages, and is consistent with paracaspase activity enhancing Malt1 scaffolding function and augmenting NFκB‐mediated transcription .…”
Section: Discussionsupporting
confidence: 58%
“…Inhibition of Malt1 paracaspase activity with 2 distinct paracaspase inhibitors, MI‐2 and MPZ, protects mice during DSS‐induced colitis . This correlates with decreased NFκB and NLRP3 activation and decreased IL‐1β and IL‐18 production by PMA‐differentiated THP‐1 cells and bone marrow macrophages, and is consistent with paracaspase activity enhancing Malt1 scaffolding function and augmenting NFκB‐mediated transcription . In contrast, mice deficient in Malt1 paracaspase activity ( Malt1 PD/− ) do significantly worse than their Malt1‐sufficient counterparts ( Malt1 +/− ) during DSS‐induced colitis .…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The colitis model was established by DSS induction according to a previous description [18]. Briefly, we divided eighteen 10-week-old male C57BL6 mice into 3 groups: healthy control group (n=6), DSS-treated group (n=6), and MIMP-treated group (n=6).…”
Section: Methodsmentioning
confidence: 99%